Tomato powder in laying hen diets: effects on concentrations of yolk carotenoids and lipid peroxidation - Akdemir, F.; Orhan, C.; Şahin, Nurhan.; Şahin, Kazım; Hayirli, A. (Taylor & Francis Ltd, 2012)
1. The effects of tomato powder supplementation on performance, egg quality, serum and egg yolk carotenoids, vitamins and malondialdehyde (MDA) concentrations in were investigated in laying hens in mid-lay. 2. A total of 90 laying hens, 49 weeks old, were divided into 3 groups consisting of 6 replicate cages, 5 birds per cage. Birds were randomly fed on one of three diets: basal diet and basal diet added with 5 or 10 g tomato powder per kg diet. 3. As tomato powder concentration increased, there were linear increases in feed intake, egg production, egg weight and yolk colour and a linear decrease in feed conversion. Shell weight, shell thickness and Haugh unit remained unchanged in response to dietary treatments. 4. Concentrations of serum and egg yolk lycopene, beta-carotene, lutein and vitamin A increased for both diets including tomato powder, whereas MDA decreased linearly with increasing supplemental tomato powder concentration. 5. Tomato powder supplementation increased egg production persistency and increased carotenoids and vitamin A contents in egg yolk, accompanied by reduced yolk lipid peroxidation.
Keywords: Gap Junctional Communication; Egg-Yolk; Antioxidant Status; Japanese-Quail; Vitamin-E; Oxidative Stress; Lycopene; Supplementation; Humans; Performance